Overview of Spirit Microscopic Imager Results. Issue 2 (21st February 2019) - Herkenhoff, Ken E.; Squyres, Steve W.; Arvidson, Raymond E.; Cole, Shoshanna B.; Sullivan, Rob; Yingst, Aileen; Cabrol, Nathalie; Lee, Ella M.; Richie, Janet; Sucharski, Bob; Bell, James F.; Calef, Fred; et al.
Abstract: This paper provides an overview of Mars Exploration Rover Spirit Microscopic Imager (MI) operations and the calibration, processing, and analysis of MI data. The focus of this overview is on the last five Earth years (2005–2010) of Spirit 's mission in Gusev crater, supplementing the previous overview of the first 450 sols of the Spirit MI investigation. Updates to radiometric calibration using in‐flight data and improvements in high‐level processing are summarized. Released data products are described, and a table of MI observations, including target/feature names and associated data sets, is appended. The MI observed natural and disturbed exposures of rocks and soils as well as magnets and other rover hardware. These hand‐lens‐scale observations have provided key constraints on interpretations of the formation and geologic history of features, rocks, and soils examined by Spirit . MI images complement observations by other Spirit instruments, and together show that impact and volcanic processes have dominated the origin and evolution of the rocks in Gusev crater, with aqueous activity indicated by the presence of silica‐rich rocks and sulfate‐rich soils. The textures of some of the silica‐rich rocks are similar to terrestrial hot spring deposits, and observations of subsurface cemented layers indicate recent aqueous mobilization of sulfates in places. Wind action has recently modified soils and abraded many of the rocks imaged by the MI, as observed at other Mars landing sites. Plain Language Summary: The Microscopic Imager (MI) on NASA's Spirit rover returned the highest‐resolution images of the Martian surface available at the time of the 2004–2010 mission. Designed to survive 90 Mars days (sols) and search for evidence of water in the past, Spirit returned data for 2210 sols, far exceeding all expectations. This paper summarizes the scientific insights gleaned from the thousands of MI images acquired during the last 5 years of the mission, supplementing the summary of the first 450 sols of the Spirit MI investigation published previously (Herkenhoff et al., 2006 ). Along with data from the other instruments on Spirit, MI images guided the scientific interpretation of the geologic history of the rocks and soils observed in Gusev crater on Mars. We conclude that the geologic history of the area explored by Spirit has been dominated by impacts and volcanism, and that water, perhaps very hot water, was involved in the evolution of some of the rocks and soils. More recently, winds have moved soil particles and abraded rocks, as observed elsewhere on Mars. These results have improved our understanding of Mars' history and informed planning of future missions to Mars. Key Points: During the Mars Exploration Rover Spirit mission, the Microscopic Imager returned 5, 923 full‐frame images These images have guided interpretations of the geologic history of Gusev crater on Mars A table summarizing the MI images chronologically is appended, including target/feature names and sequence identifiers for Pancam images that provide context